2015
DOI: 10.1001/jama.2015.5511
|View full text |Cite
|
Sign up to set email alerts
|

Association of MCAT Scores Obtained With Standard vs Extra Administration Time With Medical School Admission, Medical Student Performance, and Time to Graduation

Abstract: IMPORTANCE Individuals with documented disabilities may receive accommodations on the Medical College Admission Test (MCAT). Whether such accommodations are associated with MCAT scores, medical school admission, and medical school performance is unclear.OBJECTIVE To determine the comparability of MCAT scores obtained with standard vs extra administration time with respect to likelihood of acceptance to medical school and future medical student performance. DESIGN, SETTING, AND PARTICIPANTS Retrospective cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 31 publications
6
35
0
Order By: Relevance
“…3,5 These results underscore the limitations of studying isolated subtypes of disabilities (ie, only mobility impairments), which may underestimate this population. 6 The preponderance of students with ADHD, learning disabilities, and psychological disabilities suggests that these disability subtypes should be included in future research efforts, such as studies assessing the performance of appropriately accommodated students.…”
Section: Discussionmentioning
confidence: 85%
“…3,5 These results underscore the limitations of studying isolated subtypes of disabilities (ie, only mobility impairments), which may underestimate this population. 6 The preponderance of students with ADHD, learning disabilities, and psychological disabilities suggests that these disability subtypes should be included in future research efforts, such as studies assessing the performance of appropriately accommodated students.…”
Section: Discussionmentioning
confidence: 85%
“…Evidence on the fairness of using GRE scores for subgroups is typically studied via differential prediction analyses (AERA, APA, & NCME, 2014). Differential prediction for students with disabilities has been studied for applicants and enrolled students in medical (Searcy, Dowd, Hughes, Baldwin, & Pigg, 2015), law (Amodeo, Marcus, Thorton, & Pashley, 2009), and graduate schools (Braun et al, 1986). Performance differences, which are often related to differential prediction, have also been studied for prospective business school applicants who took the Graduate Management Admission Test (GMAT) with accommodations (Johnson, Rudner, & Sibert, 2008).…”
Section: Prior Research On Postsecondary Differential Predictive Studiesmentioning
confidence: 99%
“…In a study of students taking the Medical College Admissions Test (MCAT), Searcy et al (2015) reported that students with disabilities who took the test with extended time accommodations had no significant differences in average MCAT scores compared to students who reported no disabilities and had no extended time accommodations, either among the medical school applicants (d = .00) or among the enrolled students in medical schools (d = .05). Medical students with disabilities in their sample had lower UGPAs, on average, than medical students without disabilities.…”
Section: Prior Research On Postsecondary Differential Predictive Studiesmentioning
confidence: 99%
“…Discussion of student experiences with disability should be encouraged. [51], as well as on the Medical College Admissions Test (MCAT) [52]. The reasons for this discrepancy are poorly understood, and a failure to examine this problem perpetuates the stigma surrounding disability and the belief that intellectual "normalcy" is necessary for "the good life.…”
Section: Teach About Disability In Medical School a National Survey mentioning
confidence: 99%